2021
DOI: 10.1097/ijg.0000000000001918
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Laser Trabeculoplasty Response Duration: Analysis of a Large Clinical Database (IRIS Registry)

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…2,[25][26][27][28][29] In patients with IOP controlled on multiple medications who may have difficulty with adherence to drops or experience adverse side effects from drops, SLT has been shown to be effective in reducing medication burden while maintaining IOP control. [30][31][32][33] Although SLT efficacy has primarily been studied in POAG and ocular hypertension, various secondary OAG subtypes have shown favorable responses. SLT can be effective in steroid-induced glaucoma.…”
Section: Principlesmentioning
confidence: 99%
See 4 more Smart Citations
“…2,[25][26][27][28][29] In patients with IOP controlled on multiple medications who may have difficulty with adherence to drops or experience adverse side effects from drops, SLT has been shown to be effective in reducing medication burden while maintaining IOP control. [30][31][32][33] Although SLT efficacy has primarily been studied in POAG and ocular hypertension, various secondary OAG subtypes have shown favorable responses. SLT can be effective in steroid-induced glaucoma.…”
Section: Principlesmentioning
confidence: 99%
“…33 Eyes that were not on any medications at baseline remained medication-free for a mean of 317.6 days after treatment. 33 A retrospective study by Ansari 55 found that SLT had a 10-year success rate of 72% (success defined as a 20% reduction of IOP from the baseline and IOP <19 mm Hg) among 108 treatment-naïve eyes of 54 patients with mild POAG. The study cohort had minimal visual field progression and no need for glaucoma surgery over 10 years.…”
Section: Outcomes and Predictors Of Successmentioning
confidence: 99%
See 3 more Smart Citations